Isolation and Morphological Identification of the Bacterial Strain Pseudomonas Chlororaphis - M. A. Qalandarova,; T. S. Xusanov,; B. A. Nigmatullayev, (American Journal of Biology and Natural Sciences, 2026)
In this article, the Pseudomonas chlororaphis bacterial strain was isolated by taking samples from the moderately saline soil of the Fergana Valley and identifying all microorganisms. The morphology of the obtained Pseudomonas chlororaphis bacterial strain was determined by Gram staining. As is known, combating plant diseases and increasing their productivity has always been an urgent issue in agriculture. It is no secret that such chemicals have a negative impact on crop quality and soil fertility. With the development of science, various biopreparations are replacing chemical drugs and fertilizers. Their use improves soil fertility and crop quality. The Pseudomonas chlororaphis strain is a bacterium that is widespread in nature in plant, soil and water ecosystems and has many positive properties.